Synthesis of low coercive BaFe12O19 hexaferrite for microwave applications in low-temperature cofired ceramic - Rane, Vivek A.; Meena, Sher Singh; Gokhale, Suresh P.; Yusuf, S. M.; Phatak, Girish J.; Date, Sadgopal K. (Journal of Electronic Materials, 2013)
Polycrystalline M-type barium hexaferrite (BaFe12O19) samples have been synthesized by solution combustion route at different pH and calcination conditions in order to reduce the coercivity for microwave applications in low-temperature cofired ceramic (LTCC) substrates. Structural, morphological, and magnetic properties of BaFe12O19 were studied by x-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), Raman spectroscopy, vibrating sample magnetometry (VSM), and Mossbauer spectroscopy. The formation of a single-phase hexagonal structure was confirmed by XRD. The Raman spectra reveal all characteristic peaks of BaFe12O19, illustrating the phase purity and crystal lattice symmetry of the synthesized material. Mossbauer spectra illustrate the existence of Fe3+ cations at all five crystallographic lattice sites. The microstructural features observed by FESEM disclose the growth of nanoregime particles into hexagonal platelet particles after calcination at temperatures from 800A degrees C to 1200A degrees C. The VSM results show a lower coercivity (1350 Oe to 3500 Oe) together with reasonably high saturation magnetization (55 emu/g to 60 emu/g) and a high bulk resistivity (> 10(9) Omega-cm) at room temperature. The dependence of magnetic and electrical properties on the preparation and processing conditions is also discussed.
Keywords: Barium hexaferrite; coercivity; LTCC; Mossbauer spectroscopy; Raman spectroscopy

Off-stoichiometric nickel cobaltite nanoparticles: thermal stability, magnetization, and neutron diffraction studies - Verma, Seema; Kumar, Amit; Pravarthana, D.; Deshpande, Aparna; Ogale, Satishchandra B.; Yusuf, S. M. (Journal of Physical Chemistry C, 2014)
In the present investigation, we report a detailed examination of the effect of off-stoichiometry introduced in NiCo2O4 by adding excess cobalt. Thus, we compare and analyze the structural and magnetic properties of the Ni075Co2.25O4 and NiCo2O4 cubic systems. A low temperature combustion method was utilized to synthesize stoichiometric (NiCo2O4) and off-stoichiometric (Ni0.75Co2.25O4) nanoparticles on a large scale. The X-ray diffraction pattern for the sample annealed at high temperature (773 K) shows the presence of a much less intense NiO phase (similar to 2-5%) in Ni0.75Co2.25O4 as compared to that in the case of NiCo2O4 sample (similar to 15-20%). The Ni 2p and Co 2p XPS spectra reveal the coexistence of Ni2+, Ni3+, Co2+, and Co3+ species on the surface of both the NiCo2O4 and Ni0.75Co2.23O4 samples in differing proportions. In addition to the basic magnetic characterizations using PPMS, these were also analyzed by neutron diffraction. The off-stoichiometric Ni0.75Co2.25O4 sample shows an interesting magnetic phase conversion from frustrated dipolar system to an enhanced magnetic ordering upon annealing. Local moments on the lattice sites of NiCo2O4 and Ni0.75Co2.25O4 samples are further compared by neutron diffraction confirming stronger ordered moments and enhanced structural and thermal stability for the Ni0.75Co2.25O4 sample.

Metamagnetism in nanosheets of Co-II-MOF with T-N at 26 K and a giant hysteretic effect at 5 K - Gupta, Kriti; Dadwal, Arun; Rana, Shammi; Jha, Plawan Kumar; Jain, Anil; Yusuf, S. M.; Joy, Pattayil A.; Ballav, Nirmalya (Inorganic Chemistry, 2018)
Herein, we have synthesized at room-temperature two-dimensional nanosheets of a MOF comprised of cobalt(II) ion with benzenedicarboxylic acid ligand, which exhibited unusual magnetic properties. Direct-current magnetic susceptibility revealed an anti-ferromagnetic (AFM) transition at 26 K (Neel temperature, T-N) followed by a canting of the spin moments along with the concomitant appearance of a sigmoidal-shaped magnetization versus field (M-H) curve at 15 K. Such a canted AFM ordering led to nonzero remnant magnetization with a remarkably high coercive field of similar to 10 kOe at 5 K. Metamagnetism was further: substantiated by the alternating-current magnetic susceptibility measurements.

Exploring magnetic XY behavior in a quasi-2D anisotropic triangular lattice of Cu(II) by functionalized graphene - Gupta, Kriti; Dadwal, Arun; Jha, Plawan Kumar; Jain, Anil; Yusuf, S. M.; Joy, Pattayil A.; Ballav, Nirmalya (Inorganic Chemistry, 2020)
Study on magnetism in two-dimensional (2D) spin-lattices is advancing rapidly. In this work, phase-pure botallackite (Bo) (Cu-2(OH)(3)Br), a quasi-2D S = 1/2 anisotropic triangular spin-lattice is stabilized over 2D reduced graphene oxide (rGO) nanosheets via simple oxidation-reduction reaction chemistry. In comparison to polycrystalline Bo, such an anchoring resulted in the oriented growth of Bo crystallites in the Bo-rGO system. The Bo-rGO nanocomposite was found to be magnetically active with a Neel transition at 8.9 K, crossing over to possible XY anisotropy at similar to 5 K-as revealed by complementary dc and ac susceptibility measurements-an unprecedented observation in the field assigned to an interfacial effect. This work demonstrates the potential usage of nonmagnetic 2D functionalized graphene to significantly modulate the magnetic properties of 2D spin-lattices.

Structural, electrochemical and catalytic activity of Prussian blue analogues embedded with functionalized carbon for solid state battery applications - Shaikh, Shabana P. S.; Bhatt, Pramod; Yusuf, S. M.; Bhange, S. N.; Bansod, Sudhakar; Abdalla, Abdalla M. (International Journal of Hydrogen Energy, 2020)
The nanoparticles of Mn-1.5[Cr(CN)(6)]center dot mH(2)O@Ni-1.5[Cr(CN)(6)]center dot nH(2)O core-shell prussian blue analogues (PBA) embedded with carbon additives (PBA-C) were synthesized and characterized as electrode material for solid state battery application. The impedance spectroscopy and cyclic voltametry were used to study the electrochemical properties by adding functionalized carbon in 1:1 proportion to improve the electrical performance. The value of room temperature electrical conductivity of core-shell PBA and core-shell nanoparticles mixed with vulcan carbon (PBA-C) are found to be 1.574 x 10(-3) and 1.92 x 10(-3) Scm(-1), respectively. Using Li2La3Zr2O12 (LZZO) electrolyte, single cell was fabricated with PBA-C material, and studied its charging-discharging cycles, which exhibits higher current density with stable performance for 400 cycles for time slots of 400 min. The study reveals that the PBA core-shell nanoparticles mixed with carbon (PBA-C) may be a potential candidate as an electrode material in the form of a single cell using LZZO electrolyte. (C) 2020 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: cyclic voltametry; Electrolyte; Prussian blue analogues (PBA); Solid state battery; XPS

Possible electron doping of geometrically perfect spin-1/2 kagome-lattice barlowite by reduced graphene oxide - Gupta, Kriti; Ninawe, Pranay; Jain, Anil; Dadwal, Arun; Anas, M.; Malik, V. K.; Yusuf, S. M.; Joy, Pattayil A.; Ballav, Nirmalya (Physical Review B, 2021)
Doping of quantum spin liquid (QSL) insulators by electron or hole leads to intriguing phase transitions to metallic and superconducting states. The barlowite family with geometrically perfect S = 1/2 kagome planes and tunable interkagome coupling is an emerging platform to realize spin-ordered, valence bond crystal, QSL states. Theoretical investigations on electron doping revealed localized states in the band gap of barlowite unlike metallicity in cuprate (Nd2CuO4). We present successful anchoring of phase-pure barlowite crystallites onto reduced graphene oxide (rGO). The resulting barlowite-rGO system was found to be an electrical semiconductor with Arrhenius activation energy of 0.07 eV. Semiconducting properties of the barlowite-rGO system were further modulated with retention of structural integrity. We have attributed such a transformation of electrical transport response to plausible electron doping thereby making charge-doping experiments on barlowite and its analogs propitious.